IMPLEMENTING NIAS CULTURE-BASED LEARNING TO IMPROVE STUDENTS’ SCIENTIFIC ATTITUDES AND NUMERACY LITERACY - Darmawan Harefa (Universitas Nias Raya, 2026)
The purpose of this study was to examine the effect of implementing Nias culture-based learning on students’ scientific attitudes and numeracy literacy at SMA Negeri 1 Teluk Dalam. This research employed a quasi-experimental design with a non-equivalent control group. The population consisted of tenth-grade students, and two classes were selected as the experimental and control groups using purposive sampling. The experimental group received mathematics instruction integrated with Nias cultural elements, while the control group received conventional mathematics instruction. Data were collected through a scientific attitude questionnaire, numeracy literacy tests, and classroom observations. Descriptive and inferential statistics, including independent sample t-tests and normalized gain (N-gain) analysis, were used to analyze the data. The results indicate that students in the experimental group showed significant improvement in both scientific attitudes and numeracy literacy compared to the control group. Students demonstrated greater curiosity, critical thinking, and engagement in learning, and they were more able to apply mathematical concepts to real-life contexts. This study highlights the importance of integrating local cultural elements into mathematics education to create meaningful, contextualized learning experiences that simultaneously enhance cognitive and affective outcomes.